Pengaruh Motivasi Pembelian Dan Gaya Hidup Konsumen Terhadap Keputusan Pembelian Produk Sepatu Converse (Studi pada Mahasiswa Program Studi D-IV Manajemen Pemasaran Jurusan Administrasi Niaga Politeknik Negeri Malang Tahun Akademik 2022/2023) - Prisca Niwayanti Alecia Prisca; Eko Boedhi Santoso (CV. ITTC INDONESIA, 2025)
The purpose of this study is to determine the influence of purchase motivation and consumer lifestyle on purchase decisions for Converse footwear products. The research is quantitative with an explanatory research approach. Data collection techniques through questionnaires were given to 143 respondents who were active students of the D-IV Marketing Management Study Program, Department of Business Administration, State Polytechnic of Malang academic year 2022/2023. The sampling technique in this study is non-probability sampling with a survey or census method. This study analyzes multiple regression and hypothesis testing. The study revealed that purchasing motivation and consumer lifestyle partially and simultaneously have a positive and significant influence on the variable purchasing decision for Converse shoe products.